Develop an Empirical Formula for Grid Dependency of a PV/Battery System in Vietnam using Autoregressive Method - Nguyen, Thi Hoai Thu (Old Journal, 2018)
This paper aims at developing an empirical formula for grid dependency for PV/battery supplying to several different kinds of demand. First, the GD was calculated based on the time series of the statistic weather data at 7 locations in Vietnam over 15 years and corresponding to different capacity of PV and battery. From the results, the GD can be estimated based on the total solar radiation without the time series and the location. Then the research established a formula for GD as a function of the annual total radiation, the capacity of battery and PV using autoregressive model. The developed formula has a high accuracy in quickly estimating the GD of the system. Moreover, it was also verified by applying to another location and compared with the results obtained by directly calculating from the time series of irradiation.